Genetic diversity and differentiation among Prosopis alba (Leguminosae) populations from dry valleys of Bolivia with different levels of human disturbance and altitude - Bessega, Cecilia Fabiana (2018)
The fast expansion of human population around La Paz, Bolivia (3,200–4,100 m.a.s.l.) triggered new suburban settlements in nearby areas in valleys and mountain feet. The white mesquite, Prosopis alba Griseb. (Leguminosae), is a resource (originally used by native communities) that is strongly affected by changes in land use. A gradient in the level of disturbance is found moving away from the La Paz city toward less altitude areas. The main objective of this study was to characterize genetically three P. alba populations with different levels of human disturbance located at different altitudes in Bolivia, in order to provide some guidelines for management and conservation of these species. Based on 10 SSR loci, the populations showed high level of genetic diversity in comparison with other forest species. The population less disturbed and situated at the lowest altitude was the most variable (He = 0.51–0.42), whereas the less variable was the most disturbed and situated at the highest altitude. Heterozygote excess was observed in all populations. Most of genetic diversity (99%) is contained within populations. Genetic differentiation among populations is low (1%), suggesting low gene flow among populations. No evidence of recent bottlenecks events was detected. The estimates of the effective population size were low in all populations. The results are in agreement with the hypothesis that genetic diversity is reduced by the impact of anthropic disturbance in the population located at higher altitude in comparison with the lightly disturbed situated at lower altitude and farther from urban settlements.